Successful Management of Pediatric Todani Type IVa Choledochal Cyst with Roux-en-Y Reconstruction: Diagnostic and Surgical Insights - Rizky Ratria Kusumawardhani; Thomas Aribowo (HM Publisher, 2025)
Choledochal cysts (CC), or biliary cysts, are congenital dilatations of the biliary tree. Type IVa cysts, involving both intra- and extrahepatic ducts, present diagnostic and management challenges, particularly due to the risk of complications like cholangitis, pancreatitis, and long-term malignancy. Early diagnosis and complete surgical excision with biliary reconstruction are paramount. We report the case of a 4-year-old boy presenting with a six-month history of worsening intermittent upper abdominal pain, nausea, and vomiting. The initial ultrasound suggested a hepatic cyst. Magnetic Resonance Cholangiopancreatography (MRCP) confirmed multiple cystic dilatations involving the intra- and extrahepatic biliary ducts, consistent with a Todani Type IVa choledochal cyst. Laboratory findings showed elevated Gamma GT (179 U/L) but normal bilirubin levels. The patient underwent successful open surgery involving complete excision of the extrahepatic cyst and biliary reconstruction via Roux-en-Y hepaticojejunostomy. His postoperative course was uneventful, with discharge on day six. Follow-up revealed good clinical recovery without immediate complications. In conclusion, Todani Type IVa choledochal cysts are complex anomalies requiring meticulous diagnostic workup and tailored surgical management. This case highlights the utility of MRCP in delineating complex biliary anatomy and reaffirms Roux-en-Y hepaticojejunostomy following complete cyst excision as an effective treatment, offering favourable short-term outcomes in pediatric patients.